2020
DOI: 10.31234/osf.io/mp2xc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Play-based interventions to support social and communication development in autistic children aged 2-8 years: A scoping review

Abstract: Play is often considered by practitioners to be a natural and enjoyable context for providing intervention and support to autistic children. However, the literature on play-based interventions is large and heterogeneous.This means it is challenging for families and practitioners to navigate the evidence base and make choices about differing play-based approaches. This review aims to provide a comprehensive map of the research on this topic and to develop a conceptual framework to inform decision-making.We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Fifthly, using Reichow et al's (2008) quality criteria, the vast majority of studies in this review were classified as weak or adequate. This finding supports recommendations by Gibson et al (2020) (Gibson et al, 2020;Ke et al, 2018;Lindsay et al, 2017).…”
Section: Recommendations For Future Practice-based Research In the Field Of Autism Play And Social Communication Developmentsupporting
confidence: 90%
See 4 more Smart Citations
“…Fifthly, using Reichow et al's (2008) quality criteria, the vast majority of studies in this review were classified as weak or adequate. This finding supports recommendations by Gibson et al (2020) (Gibson et al, 2020;Ke et al, 2018;Lindsay et al, 2017).…”
Section: Recommendations For Future Practice-based Research In the Field Of Autism Play And Social Communication Developmentsupporting
confidence: 90%
“…Finally, the majority of studies consisted of naturalistic behavioural approaches (e.g. Chang et al, 2016b;Goods et al, 2013;Lawton & Kasari, 2012;Thomas & Smith, 2004;Vincent et al, 2018) similar to findings reported in other systematic reviews in the field (Gibson et al, 2020;Kossyvaki & Papoudi, 2016). This is unsurprising given the current shift within the literature towards an integrated approach to learning involving both behavioural and developmental approaches for children with ASD (Frost et al, 2020;Hume et al, 2021;Schreibman et al, 2015).…”
Section: Research On Play-based Interventions For the Social Communication Skills Of Children With Asd In Educational Settingssupporting
confidence: 57%
See 3 more Smart Citations